Evaluation of a strategy for tumor-initiating stem cell eradication in primary human glioblastoma cultures as a model - E. V. Dolgova; A. S. Proskurina; E. A. Potter; T. V. Tyrinova; O. S. Taranov; Ya. R. Efremov; K. E. Orishchenko; S. V. Mishinov; V. V. Stupak; A. A. Ostanin; E. R. Chernykh; S. S. Bogachev (Вавиловский журнал генетики и селекции)
Primary cultures of human glioblastoma were obtained from the surgical material of patients K. (female, 61 years, Ds: relapse of glioblastoma) and Zh. (female, 60 years, Ds: relapse of glioblastoma). The effectiveness of a new therapeutic approach aimed at destroying the cancer cell community was evaluated on the primary cell lines of human glioblastoma culture by employing a new strategy of tumor-initiating stem cell synchronization and a domestic strategy of their eradication "3+1". The key elements of the strategy were the following indicator results: (1) evaluation of the presence of tumor-initiating stem cells in a population of cells from analyzed cultures by their ability to internalize double-stranded labeled DNA (TAMRA+ cells); (2) determination of the reference time points of the repair cycle of DNA interstrand cross-links induced by cross-linking cytostatic mitomycin C; (3) evaluation of cell cycle synchronization; (4) determination of the time (day after therapy initiation) when TAMRA+ cells were synchronously present in phase G1/S of the cell cycle, sensitive to the therapy; and (5) establishment of the TAMRA+ (tumor-initiating stem cells) eradication schedule. The cultures were treated with cross-linking cytostatic mitomycin C and a compositional DNA preparation. After the treatments, cell division slows down, and the cultures degrade. The K cell line completely degraded within 30 days of observation. The cell number of the Zh culture fell to nearly one-third of the starting value by day 15 of observation. On day 15, this indicator constituted 1/7.45 for mitomycin C and 1/10.28 for mitomycin C + DNA with reference to the control. The main target of the mitomycin C + DNA regimen was TAMRA+ tumor-initiating stem cells of the glioblastoma cell populations. The action of mitomycin C alone or in the combination with DNA demonstrated effective elimination of TAMRA+ tumor-initiating stem cells and the whole primary cultures of human glioblastomas.